Co-conjugation of Virulence Plasmid and KPC Plasmid in a Clinical Klebsiella pneumoniae Strain - Yang, Xuemei; Dong, Ning; Liu, Xiaoxuan; Yang, Chen; Ye, Lianwei; Chan, Edward Wai-Chi; Zhang, Rong; Chen, Sheng (Frontiers in Microbiology, 2021)
Carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-HvKP) strains have been increasingly reported and it is important to understand the evolutionary mechanisms of these highly pathogenic and resistant bacterial pathogens. In this study, we characterised a ST11 carbapenem-resistant K. pneumoniae strain which harbored an IncFIB/IncHI1B type virulence plasmid and an IncFII/IncR type blaKPC-2-bearing plasmid. The virulence plasmid was found to be conjugative and harbored a 35-kbp fragment including aerobactin encoding cluster from virulence plasmid pLVPK and multiple resistance genes, resulting in a mosaic multi-drug resistance and virulence plasmid. This virulence plasmid could be transferred via conjugation to Escherichia coli and Klebsiella pneumoniae strains alone as well as together with the blaKPC-2-bearing plasmid. Co-transmission of virulence and blaKPC-2-bearing plasmids would directly convert a classic K. pneumoniae strain into CR-HvKP strain, leading to a sharp increase in the prevalence of CR-HvKP in clinical settings, which poses a great threat to human health.